(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aimed to identify the impact of the internal auditor evaluation on developing the accounting information system at the mineral oils mixing and bottling plant in Zawiya, western Libya. To achieve the study’s objectives, the descriptive-analytical method was adopted, and a questionnaire was used as the main tool to collect data from a sample of internal auditors and accountants in the general accounts department of the company owning the plant under study. The study found that the impact of internal audit evaluation on developing the accounting system is weak. The results showed that some aspects related to internal auditing do not contribute positively to development by enhancing financial control and improving the efficiency of financial reports, while other aspects did not show a clear effect. The study recommended working on strengthening the role of internal auditors and updating procedures to align with modern auditing standards to improve financial evaluation efficiency and develop the accounting information system.